Respuesta :

-5 = [tex] \frac{3}{4} x[/tex] - 2 equals x = -4.

First, simplify [tex] \frac{3}{4} x[/tex] to [tex] \frac{3x}{4} [/tex]. / Your problem should look like: -5 = [tex] \frac{3x}{4} [/tex] - 2.
Second, multiply both sides by 4. / Your problem should look like: -20 = 3x -8.
Third, add 8 to both sides. / Your problem should look like: -20 + 8 = 3x.
Fourth, simplify -20 + 8 to -12. / Your problem should look like: -12 = 3x.
Fifth, divide both sides by 3. / Your problem should look like: [tex]- \frac{12}{3} [/tex] = x.
Sixth, simplify [tex] \frac{12}{3} [/tex] to 4. / Your problem should look like: -4 = x.
Seventh, switch sides. / Your problem should look like: x = -4, which is your answer.